Prevalence and risk factors of acute respiratory infection among school children in coastal South India - E Suguna; S Ganesh Kumar; Gautam Roy (Journal of Global Infectious Diseases, 2014)
Background and Objectives: There is a paucity of information available on acute respiratory infection (ARI) among school children in India. This study was aimed to assess the prevalence and certain risk factors associated with ARI among school children. Materials and Methods: This cross-sectional study was conducted among 397 school children age group of 5-14 years in the seven schools of rural Puducherry, India. Data on socio-demographic characteristics and associated risk factors of ARI were collected by interview using pre-tested structured questionnaire. Data was analyzed by univariate and multiple logistic regression analysis. Results: Overall, 51.1% (203) of the subjects had at least one symptom of ARI in the preceding 2 weeks. The manifestations of ARI included allergic rhinitis (183, 46.1%), dry cough (75, 18.9%), throat pain and fever (54, 13.6%), wheezing (39, 9.8%) and ear discharge (28, 7.1%). About half of the subjects with ARI (52.2%) belonged to 5-9 year age group and females (52.3%). Mother′s education, family history of allergic disorder and asthma, absence of smoke outlet in kitchen and windows in sleeping room were found to be significantly associated with ARI in univariate analysis (P < 0.05). Multiple logistic regression analysis showed that 5-9 years age group (odds ratio [OR] = 1.7), family history of allergic disorder (OR = 9.6) and asthma (OR = 5.2), presence of smoke outlet in kitchen (OR = 0.5), absence of windows in sleeping room (OR = 3.0) were found to have an independent association with the ARI. About 29.6% (60) of the subjects with ARI had accessed health care facility for treatment. Conclusion: ARI among school children is an important health problem. Interventions like provision of smoke outlets and windows in sleeping room may help in reduction of burden of ARI.